Boost Cascaded Paralleled Dual Buck-Boost Multi-Output Non-Isolated Hybrid Converter with Reduced Leakage Current - Keshari R.K.; Singh R.K. (My University, 2025)
This paper proposes a multi-output hybrid converter with the idea of boost cascaded with the paralleled dual buck-boost converter to achieve boost DC and AC output simultaneously from a single photovoltaic (PV) source. A stray capacitance (CPV) is formed between a large PV panel and the ground; therefore, a high-frequency voltage appears across CPV. As a result, a strong leakage current causing power loss and safety issues circulate into the system. To cope with the circulating leakage current, a bulky, lossy, and costly isolation transformer is introduced on the AC side of the hybrid converter. On the other hand, the same set of switches operates in a hybrid converter; therefore, there is a compromise between duty ratio (d) and modulation index (mi) as d+mi< 1. The proposed non-isolated hybrid converter, along with a novel PWM scheme, is capable of reducing the leakage current significantly. Moreover, the AC section of the hybrid converter can achieve unity gain at a mi of 0.5, concerning the conventional topologies where the gain of 0.5 is obtained at the mi of 0.5. A 200 W laboratory prototype is developed and tested using an F28335 digital signal processor to validate the proposed hybrid converter. © 2022 IEEE.